A 14, 000-year record of fire, climate, and vegetation from the Bear River Range, southeast Idaho, USA. (June 2016) - Lundeen, Zachary J; Brunelle, Andrea
The vegetation and fire history of the Bear River Range (BRR), Southeast Idaho has been reconstructed from pollen, plant macrofossils, and macroscopic charcoal from lacustrine sediments. Overall, the BRR record shows independent responses of vegetation and fire regime to climate variation. The reconstructions suggest strong seasonal bias from the proxies evaluated, with the pollen record most sensitive to insolation-driven summer temperature trends, and the charcoal-based fire record more sensitive to winter snowpack variability. Together, the proxies suggest that the early Holocene experienced larger than average snowpacks but very warm summers. Warmer than modern summer temperatures were maintained through much of the mid-Holocene, but snowpacks decreased dramatically, creating the most extreme xeric conditions in the Holocene between ~7100 and 6000 BP. After 6000 BP, summers began to show a consistent cooling trend. Winter precipitation remained low until ~4400 BP, after which higher than average snowpacks are indicated until 2000 BP. Pollen and charcoal data relationships at ~8800 BP and from 1800 to 800 BP suggest periods with anomalously wet summers that created a unique fire regime during those intervals.